Effectiveness of Audio–Video Material in Teaching-Learning Process at Secondary Stage - Tanwar, Pramila (SCHOOL SCIENCE, 2017)
This work is based on the use of audio-video resources in few schools of Delhi NCR with specific reference to five secondary schools opted for this study. The study had following purposes information about the types of audio-video teaching materials available in the schools, the frequency of their use, the steps school has taken in promoting the use of audio-video resources and the effectiveness of these resources in the teaching-learning process. Four questionnaires were administered in each school; two sets to science lecturers, one set to students and one set to administrative staff in order to explicate the above information. Data were collected, coded and analysed using statistical techniques like percentages for the easy analysis of data. Finally, it was unearthed that the schools collection of audio-video materials was inadequate. Audio-video materials were hardly used by the teachers for teaching. The only medium of instruction used was chalkboard method. Non-availability of e-resources, lack of supporting ICT infrastructures and lack of awareness about the utility of these e-resources in these schools was recorded. There are numerous benefits that students derive from the use of audio-video materials. The awareness of available audio-video resources created by these schools was not imposing.